Group Work in Career Development: Status Quo and Future Agenda. Issue 2 (3rd April 2021) - McMahon, Mary; Watson, Mark
ABSTRACT: The status quo and future agenda of group work in career development are considered in this article which represents the culmination of a two-part special issue published on this topic in the Journal for Specialists in Group Work . Following an enthusiastic response to the call for papers, 15 articles were accepted and resulted in two consecutive parts of the special issue being published. The first part contained nine articles focused on school age populations and this second part comprises six articles focused on post-school age populations. This article discusses the commonalities and divergences between the articles published in the two parts of the special issue and offers suggestions related to the future of group work in career development.